ORGANIZATIONAL CULTURE AS A SUBJECT OF SOCIAL SCIENCES: HISTORY OF STUDY AND DETERMINATION OF THE CONCEPT BOUNDARIES - E. V. Strogetskaya (Дискурс, 2017)
The article is devoted to the systematization of approaches in understanding the phenomenon of organizational culture. The reasons of interest in this phenomenon in various countries of the world are revealed. Gnoseological sources of the concept «organizational culture» and the evolution of the concept in scientific discourse are considered. Socio-psychological, anthropological and sociological preconditions for the creation of a general theory of organizational culture which gained rapid development in the 70-80s of the XX century are analyzed. The contribution of sociology to the development of this theory is determined. The mutual influence and the difference between such related terms as «organizational culture» concepts like organizational morality, organizational behavior, organizational climate, organizational consensus and corporate identity are established. The concepts «organizational culture» and «corporate culture» are differentiated. The methodological advantages of the concept «organizational culture» as applied to the sociological analysis of the organization are substantiated.